Social networks as a key strategy for positioning coffee shops in the digital era - Lázaro Merino, Mirella; Mendo-Ruiz, Olenka Marylin; Lazaro Acero, Heli Modesto; Suxe-Ramírez, María Alicia (LACCEI, 2025)
The purpose of the following study was aimed at determining the existence of a link in terms of social media strategies and the positioning of coffee shops among consumers in Nuevo Chimbote, 2024. In this case, a methodology was used that includes a quantitative approach with a correlational scope. The study units that made up the sample were 80 young people between 20 and 35 years old, all belonging to the urban area of the town of Nuevo Chimbote, who consume in coffee shops. Also, the survey conducted in Google Forms was used as a technique to collect the appropriate information. The data collected from the study were processed in the SPSS statistical application. As a result of the study, the alternative hypothesis was confirmed through the application of the instrument in which a moderate positive Spearman statistical correlation of 0.513 was reached between the study variables and a significance level of 0.000. Therefore, it can be concluded from the research that social networks have a favorable influence on the behavior of customers regarding their consumption in coffee shops.